Water War Thesis: Perspective from South Asia - Muhammad Imran Mehsud; Tariq Anwar Khan (Journal of Political Studies, 2019)
Water war thesis argues that water scarcity due to climate change and population surge has resulted in water disputes in different arid regions of the world. Absence of water treaties amongst co-riparian states of a river, or stress in the treaties, hydrohegemonic behavior, and deviation from international water law on the part of a regional power, domestic water disputes and the subsequent pressures for more water could snow ball the water disputes into water wars. Such a water war could take place in the Middle East. This paper analyzes the basis premises of the water war thesis in the context of regional hydro-politics of South Asia. It argues that the region of South Asia is equally vulnerable to the water war thesis and recommends serious consideration.